Overexpression of A Biotic Stress-Inducible Pvgstu Gene Activates Early Protective Responses in Tobacco under Combined Heat and Drought - Stavridou, Evangelia (Int J Mol Sci, 2021)
Drought and heat stresses are major factors limiting crop growth and productivity, and their effect is more devastating when occurring concurrently. Plant glutathione transferases (GSTs) are differentially expressed in response to different stimuli, conferring tolerance to a wide range of abiotic stresses. GSTs from drought-tolerant Phaseolus vulgaris var. “Plake Megalosperma Prespon” is expected to play an important role in the response mechanisms to combined and single heat and drought stresses. Herein, we examined wild-type N. tabacum plants (cv. Basmas Xanthi) and T1 transgenic lines overexpressing the stress-induced Pvgstu3–3 and Pvgstu2–2 genes. The overexpression of Pvgstu3–3 contributed to potential thermotolerance and greater plant performance under combined stress. Significant alterations in the primary metabolism were observed in the transgenic plants between combined stress and stress-free conditions. Stress-responsive differentially expressed genes (DEGs) and transcription factors (TFs) related to photosynthesis, signal transduction, starch and sucrose metabolism, osmotic adjustment and thermotolerance, were identified under combined stress. In contrast, induction of certain DEGs and TF families under stress-free conditions indicated that transgenic plants were in a primed state. The overexpression of the Pvgstu3–3 is playing a leading role in the production of signaling molecules, induction of specific metabolites and activation of the protective mechanisms for enhanced protection against combined abiotic stresses in tobacco.